Experimental Study on Fatigue Characteristics and Life Prediction of Rotating Restricted Short Suspender in Suspension Bridge - Lei Zhao; Zhili Yang; Xianneng Tong; Yang Zhang; Ruifeng Nie (Buildings)
The corrosion of the rotating axis pins of the short suspender will lead to the rotating restriction of its end, which will lead to the corrosion of the parallel wires and affect the performance of the short suspender. In this study, the technical condition of the rotating restricted short suspender unfixed from the suspension bridge was carefully detected. An axial tensile performance test was carried out on these short suspenders, and the subsequent availability of the rotating restricted suspender was evaluated based on the size of the fracture gap. The rotationally limited working conditions of these short suspenders were skillfully simulated by the specially designed tooling, and the fatigue performance test of the rotating restricted short suspender was carried out. A simplified simulation method was proposed based on the random traffic theory. By introducing traffic data obtained from the WIM system, the stress response of the short suspenders caused by vehicles on each lane was simulated, and the simulation results were converted by the rain flow counting method. The residual life of the rotating restricted short suspender was predicted by the comparison between the fatigue test results and the fitting curve of the simulation results. From this study, several of the following conclusions can be summarized: The measured fracture gap size is negatively correlated with the effective area of the suspender, and the gap size of 8mm is a key value. When the fatigue load cycle reaches 345,000 times, the suspender is already in a dangerous state. Additionally, the fractured gap size is considered as the judgment basis for the usability of rotating restricted short suspenders. When the gap size is less than 8 mm, the suspender can be continually used after maintenance and should be updated after 6 years. Otherwise, the suspender needs to be replaced immediately.